Estimation of Default Probability for Corporate Entities in Republic of Serbia - Vujnovic, Milos; Bogojevic Arsic, Vesna; Nikolic, Nebojsa (Industrija, 2016)
In this paper a quantitative PD model development has been excercised according to the Basel Capital Accord standards. The modeling dataset is based on the financial statements information from the Republic of Serbia. The goal of the paper is to develop a credit scoring model capable of producing PD estimate with high predictive power on the sample of corporate entities. The modeling is based on 5 years of end-of-year financial statements data of available Serbian corporate entities. Weight of evidence (WOE) approach has been applied to quantitatively transform and prepare financial ratios. Correlation analysis has been utilized to reduce long list of variables and to remove highly interdependent variables from training and validation datasets. According to the best banking practice and academic literature, the final model is provided by using adjusted stepwise Logistic regression. The finally proposed model and its financial ratio constituents have been discussed and benchmarked against examples from relevant academic literature.